Effect of RF Power on the Physical Properties of Sputtered ZnSe Nanostructured Thin Films for Photovoltaic Applications - Ovidiu Toma (MDPI AG, 2021)
Zinc selenide (ZnSe) thin films were deposited by RF magnetron sputtering in specific conditions, onto optical glass substrates, at different RF plasma power. The prepared ZnSe layers were afterwards subjected to a series of structural, morphological, optical and electrical characterizations. The obtained results pointed out the optimal sputtering conditions to obtain ZnSe films of excellent quality, especially in terms of better optical properties, lower superficial roughness, reduced micro-strain and a band gap value closer to the one reported for the ZnSe bulk semiconducting material. Electrical characterization were afterwards carried out by measuring the current–voltage (I-V) characteristics at room temperature, of prepared “sandwich”-like Au/ZnSe/Au structures. The analysis of I-V characteristics have shown that at low injection levels there is an Ohmic conduction, followed at high injection levels, after a well-defined transition voltage, by a Space Charge Limited Current (SCLC) in the presence of an exponential trap distribution in the band gap of the ZnSe thin films. The results obtained from all the characterization techniques presented, demonstrated thus the potential of ZnSe thin films sputtered under optimized RF plasma conditions, to be used as alternative environmentally-friendly Cd-free window layers within photovoltaic cells manufacturing.